GP293 Developing MARSIPAN integrated care pathways for children and adolescents with eating disorders- real world challenges and recommendations. (June 2019) - Carter, Michael; Garvey, Aisling; Gibson, Louise; McDevitt, Sara
Abstract : Background: Anorexia Nervosa has the highest rate of mortality and morbidity of the mental health conditions. Much of this is related to the physical consequences of starvation and can lead to medical admissions. Integrated care pathways have the potential to decrease admission rates, reduce duration of stay, and prevent patients slipping through gaps between services. The Junior MARSIPAN risk assessment guideline is a best practice framework that has potential to enhance integrated decision making between mental health, paediatric and primary care for children and adolescents with eating disorders. Objective: To explore the use of Junior MARSIPAN risk guidelines in collaborative decision making in a Regional Tertiary Referral Hospital, and to understand any associated barriers and enabling factors in their implementation. Methods: Patients discharged from Cork University Hospital with a diagnosis of Anorexia Nervosa/Eating Disorder were identified using HIPE data, over a 2-year time period. Variables collected included: admission and subsequent number of bloods performed, assessment of cardiovascular stability, contact with Child and Adolescent Mental Health Service (CAMHS), MDT meetings, the presence of psychiatric co-morbidities and evidence of discharge planning. Results: Of the 38 patients who presented to hospital, 20 were identified as having been admitted overnight over the time period, involving 16 patients. The mean number of admissions per patient was 4(2–11), mean age 15.1years (9.6–17.8 y) and 14 were female. The majority of admissions (68%) were unplanned and most were self-referrals. A total of 11 physicians were involved in the care in addition to 6 CAMHS teams and 2 GPs. There was inadequate evidence of documentation of physical risk parameters (BMI%, Orthostatic BP), biochemistry for monitoring of refeeding syndrome, and of multidisciplinary approach to care and discharge planning. Conclusions: Complexity and delayed communication was a significant barrier to the implementation of junior MARSIPAN across the 17 different teams involved. There is a need to develop MARSIPAN Lead clinician 'champions' and to standardised approaches across services, adult, Paediatric and child psychiatry, in order to minimise variability in patient clinical care experience. An integrated care pathway, based on the Junior MARSIPAN Guidelines, is proposed to improve initial assessment, inpatient management of refeeding risks and to plan discharge. It is hoped this will lead to safer, more supportive and seamless care for young people with eating disorders when they become medically unstable.